Construction and Comprehensive Analysis of the ceRNA Network to Reveal Key Genes for Benign Tracheal Stenosis - He, Yanpeng; Zou, Chunyan; Cai, Zhigang (Frontiers in Genetics, 2022)
Objective: To explore the possible biological functions of the differentially expressed genes in patients with benign tracheal stenosis, and to provide a valuable molecular basis for investigating the pathogenesis of benign tracheal stenosis. Method: Whole transcriptome sequencing was performed on blood samples collected from patients with benign tracheal stenosis and normal controls. Differentially expressed mRNA, lncRNA and circRNA were analyzed using the DESeq2 package. The protein interaction networks for differentially expressed mRNAs were constructed by STRING. The results of gene co-expression network analysis, Starbase database prediction, and differential gene expression were combined to construct a competing endogenous RNA network. The transcription factors of key genes were predicted using NetworkAnalyst database and a transcription factor-mRNA regulatory network was constructed. The classical pathways, intermolecular interaction networks, and upstream regulatory components of key genes were analyzed using Ingenuity Pathway Analysis (IPA). Finally, the DGIDB database was used to predict the potential therapeutic drugs to target the identified key genes. Result: A total of 852 differentially expressed RNA species were obtained from the analysis, including 229 mRNAs, 40 lncRNAs, and 583 circRNAs. The 229 mRNAs were associated with oxygen transport, neutrophil activation, immune response, and oxygen binding. PPI network analysis generated 160 protein-protein interactions, and yielded 46 key genes. Then, we constructed a "lncRNA-miRNA-mRNA" network consisting of 8 lncRNAs, 31 mRNAs, and 116 miRNAs, and a "circRNA-miRNA-mRNA" network including 30 circRNAs, 36 mRNAs, and 275 miRNAs. IPA analysis showed that the 46 key genes were significantly associated with inflammatory activation and acute respiratory distress syndrome. The constructed TF-mRNA regulatory network was composed of 274 nodes and 573 interacting pairs. 251 potential therapeutic drugs were identified from the DGIDB database. Conclusion: This study analyzed the differential genes associated with benign tracheal stenosis and explored the potential regulatory mechanisms, providing a scientific reference for further studies on the pathogenesis of benign tracheal stenosis. Keywords: benign tracheal stenosis; differential analysis; competing endogenous RNA; PPI; transcriptome sequencing; bioinformatics